Remittance Volatility and Social Development in Nepal: A GARCH-MIDAS Approach to Understanding Economic Stability’s Impact on Education and Community Welfare - Adhikari, Gyan Mani; Duwal, Bal Ram; Chhetri, Santosh (Molung Educational Frontier, 2026)
This study investigates the relationship between remittance volatility and social development outcomes in Nepal, employing the Generalized Autoregressive Conditional Heteroskedasticity Mixed Data Sampling (GARCH-MIDAS) model within a social development theoretical framework. Grounded in development economics and volatility theory, this research examines how remittance fluctuations impact not only macroeconomic stability but also critical social indicators, including educational access, healthcare utilization, and community development initiatives. Nepal, as one of the world’s largest remittancereceiving countries, with remittance inflows exceeding 25% of GDP, provides an ideal case study for understanding how remittance volatility affects economic indicators and social outcomes. Using quarterly data from 2000 to 2024, we organize remittance volatility into short- and long-term components, incorporating macroeconomic variables and social development indicators at different frequencies. Our findings reveal that remittance volatility significantly impacts Nepal’s social development trajectory, with asymmetric effects across various time horizons. Short-term remittance volatility primarily affects household educational expenditure and healthcare spending, while long-term volatility influences community infrastructure development, gender equity in education, and rural development initiatives. This study investigates the relationship between remittance volatility and social development outcomes in Nepal, employing the Generalized Autoregressive Conditional Heteroskedasticity Mixed Data Sampling (GARCH-MIDAS) model within a social development theoretical framework. Grounded in development economics and volatility theory, this research examines how remittance fluctuations impact not only macroeconomic stability but also critical social indicators, including educational access, healthcare utilization, and community development initiatives. Nepal, as one of the world’s largest remittance receiving countries, with remittance inflows exceeding 25% of GDP, provides an ideal case study for understanding how remittance volatility affects economic indicators and social outcomes. Using quarterly data from 2000 to 2024, we organize remittance volatility into short- and long-term components, incorporating macroeconomic variables and social development indicators at different frequencies. Our findings reveal that remittance volatility significantly impacts Nepal’s social development trajectory, with asymmetric effects across various time horizons. Short-term remittance volatility primarily affects household educational expenditure and healthcare spending, while long-term volatility influences community infrastructure development, gender equity in education, and rural development initiatives. The GARCH-MIDAS framework demonstrates superior forecasting performance relative to traditional GARCH models, achieving 15-23% higher accuracy across key social indicators. The results suggest that while remittances are crucial drivers of social development, their volatility can undermine educational progress and social equity